Examining the Usage of Instagram as the Strategy to Build the Brand Value of PT Ayo Media Network - Muhammad Zindan Taufikurrahman; Cecep Barkah (Research and Community Service INSTITUT TEKNOLOGI DAN BISNIS KALBIS, 2023)
In this digital era, social media has become an essential tool in marketing strategy and building brand value. Brand value is a valuable asset, which includes the perceptions and values associated with the brand. PT Ayo Media Network, one of the largest media companies in West Java, is a media company that continues to operate and develop to this day. This article will examine how customer interaction through PT Ayo Media Network Bandung's Instagram account can provide a positive and valuable experience, ultimately increasing the company's brand value. This research uses a qualitative research method with a SWOT analysis approach. From the data analysis conducted, it was found that the company's strengths were still more significant or dominant compared to its weaknesses and opportunities that are still more powerful than the threats the company must overcome. That way, the company is found to be in quadrant one position.